PENGARUH PERSEPSI HARGA DAN KEPERCAYAAN TERHADAP MINAT BELI SECARA ONLINE SAAT PANDEMI COVID-19 PADA MASYARAKAT MILLENIA DI JAWA TENGAH - Kusumawati, Dyah; Saifudin, Saifudin (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This study was conducted to examine the extent of the influence of price perceptions and confidence in online buying interest during the Covid-19 pandemic in the millennial community in Central Java. This type of research is explanatory research. The population is all millennia in Central Java who use online purchasing facilities. The technique of determining the sample by means of convenience sampling. In this study the number of samples used 234 respondents. Data analysis was performed using multiple linear regression analysis techniques. Data collection techniques through online questionnaires using a Likert scale. Data sources are primary data and secondary data. The result is based on partial testing in this study, the price has no significant effect on buying interest, while trust has a positive and significant effect on buying interest. Based on the results of simultaneous testing although weak, simultaneously price and trust have positive and significant effect on online buying interest.Â Keywords: price perception, trust, buying interest